Keeping things under control: exploring migrant Eastern European womens' experiences of pregnancy in Ireland. (7th August 2016) - Dempsey, Maria; Peeren, Siofra
Abstract: Objective: This study explores migrant Eastern European women's experience of pregnancy in Ireland. It contributes to understanding how the migration process may impact on pregnancy and motherhood. Method: Interviews were conducted with 12 Eastern European women, aged between 20 and 40 years, who had experienced, or who were experiencing, pregnancy in Ireland. Data were analysed using the grounded theory method. Results: A core category of 'keeping things under control' comprising three themes: 'balancing conflicting demands', 'reconstructing cultural heritage' and 'negotiating discrepancies between expectations and reality' was identified. The findings advance understanding of how migrant women try to gain control over their new life while managing two transformative life events: pregnancy and migration. Conclusions: Migrant women who experience pregnancy in their host country face multiple, multi-faceted challenges, which have bidirectional relationships with social support. Migrant Eastern European women may have particular struggles with transitioning to a less medicalised maternity healthcare system when they migrate to Ireland.